Isolation of the 67Gallium Accumulating Fraction in Normal Rat Liver - Hierholzer, K.; zum Winkel, K.; Aulbert, E.; Haubold, U. (Nuklearmedizin - NuclearMedicine, 1974)
Subcellular 67Gallium distribution was investigated in normal rat liver after intravenous injection. By differential centrifugation and density gradient centrifugation 67Gallium accumulating bodies were isolated and identified as lysosomes by enzyme determination and electron microscopy. 67Gallium enrichment in this fraction was 23-fold. Using the isolated 67Gallium accumulating lysosomes the binding state of the isotope inside the lysosomes was studied. 67Gallium was found to be associated with the soluble fraction of lysosomes.